Vaccine Side Effects Following COVID-19 Vaccination Among the Residents of the UAE—An Observational Study - Ganesan, Subhashini; Al Ketbi, Latifa Mohammad Baynouna; Al Kaabi, Nawal; Al Mansoori, Mohammed; Al Maskari, Noura Nasser; Al Shamsi, Mariam Saif; Alderei, Aysha Saeed; El Eissaee, Hamada Nasser; Al Ketbi, Rudina Mubarak; Al Shamsi, Noura Saeed; Saleh, Khuloud Mohammed; Al Blooshi, Aysha Fahad; et al. (Frontiers in Public Health, 2022)
COVID-19 vaccines have proven to be very safe in the clinical trials, however there are very few evidences comparing the safety of these vaccines on real-world settings. Therefore, we aim to investigate the nature and severity of adverse effects reported and the differences based on the type of vaccine received. A survey was conducted among 1878 adult (≥ 18 years) COVID-19 vaccine recipients through online survey platforms and telephonic interviews during the period from March to September 2021. Factors potentially associated with reported side effects like age, gender, ethnicity, comorbidities and previous COVID-19 infection were analyzed based on the type of vaccine received. Differences in the nature of adverse events and the severity were compared between inactivated and mRNA vaccine recipients. The major adverse effects reported by the COVID-19 vaccine recipients were pain at the site of injection, fatigue & drowsiness and headache followed by joint/muscle pain. The adverse effects were more common among recipients of mRNA Pfizer-BioNTech vaccine than among recipients of inactive Sinopharm vaccine with the odds ratio of 1.39 (95% CI 1.14-1.68). The average number of adverse effects reported between individuals who had received Sinopharm and Pfizer-BioNTech vaccine were 1.61±2.08 and 2.20±2.58 respectively and the difference was statistically significant (p<0.001). Severe adverse effects after COVID-19 vaccinations were rare and 95% of the adverse effects reported after either an inactivated or mRNA vaccine were mild requiring no or home-based treatment. The study found that individuals who are less than 55 years of age, female gender, has one or more comorbid conditions, who have received mRNA Pfizer- BioNTech vaccine and has history of COVID-19 infections are at higher odds of developing an adverse effect post vaccination than the others.